Sound Choreography <> Body Code : Software Deployment and Notational Engagement without Trace. - Sicchio, Kate; McLean, Alex (Contemporary Theatre Review, 2017)
This paper introduces our collaborative work Sound Choreography <> Body Code (SC<>BC), bringing choreography and computer programming together in live performance. This work connects digital abstraction and bodily movement in a feedback loop, and throws up a range of issues for our individual practices (McLean as a live coder and Sicchio as a choreographer) as well as for the growing wider field of technology-infused performance. We will focus on the different roles of notation in this performance, in the light of the three themes of the present special issue: deployment, engagement, and trace. We will begin by briefly reviewing some context before introducing the work, and conclude by directly addressing these themes.